A 2D Kaleidoscope of Electron Heat Fluxes Driven by Auroral Electron Precipitation. Issue 18 (21st September 2022) - Khazanov, George V.; Gabrielse, Christine; Glocer, Alex; Chu, Mike; Nishimura, Yukitoshi; Reyes, Pablo
Abstract: Electron heat flux is an important value for ionospheric space weather modeling networks. Utilizing the 2D array of Time History of Events and Macroscale Interactions during Substorms all‐sky‐imager (ASI) observations, Gabrielse et al. (2021, https://doi.org/10.3389/fphy.2021.744298 ) described a new method that estimates the auroral scale sizes of intense precipitating electron energy fluxes and their mean energies during two substorms on 16 February 2010. These parameters in combination with SuperThermal Electron Transport code were used to develop a new methodology to calculate electron thermal fluxes from data inputs in 2D during one of the substorms at 09:40:00 UT across Canada and Alaska. To test the effect of various precipitation lifetimes on electron heat flux values, boxcar averages ranging from 0 to 900 s were applied to the ASI data. These data are then combined with the newly developed kinetic simulation to determine the thermal fluxes associated with the observed diffuse and discrete precipitation. Plain Language Summary: Knowing the thermal electron heat flux at the upper ionospheric boundaries is the Achilles' heel of all ionospheric models. Such a thermal heat flux setting is especially difficult to justify in the region of the diffuse aurora that is connected to a large energy reservoir of electrons with energies of a few kiloelectron volts, the Earth's plasma sheet, where MI coupling processes are strongly interconnected. Utilizing the 2D array of Time History of Events and Macroscale Interactions during Substorms all‐sky‐imager white light observations, Gabrielse et al. (2021, https://doi.org/10.3389/fphy.2021.744298 ) described a new method that estimates the auroral scale sizes of intense precipitating electron energy fluxes and their mean energies during two substorms. These data are used as inputs to a numerical simulation to determine the thermal fluxes associated with the observed diffuse and discrete precipitation across Canada and Alaska. This is the first‐time data in two dimensions are used to inform a model in order to obtain the thermal electron heat flux values. The new method is an improvement over current calculations, since thermal electron heat fluxes cannot be observed directly and thus far have remained elusive and dependent on modeling assumptions. Key Points: Time History of Events and Macroscale Interactions during Substorms all‐sky imager observations are used across Canada and Alaska for first ever 2D data‐informed heat flux estimation Data from substorm case study is coupled to SuperThermal Electron Transport model for the heat flux estimation Time resolution of energy flux and mean energy inputs shown to be remarkably important in heat flux calculation